From rainfall to seafloor: Tracing riverine and urban stormwater litter transport in Mediterranean fishing grounds through systematic meteorological station testing - Xavier Garcia; Maik Neukirch; Jordi Iglesias; Elisa Berdalet; Joaquim Ballabrera-Poy; Savitri Galiana; Eva Flo; Bru Cabús; Jordi Ribera-Altimir; Marta Blanco; Eve Galimany (Environmental Pollution, 2026)

Social life cycle assessment of bio-based products from microbiomes: Additives, bioplastics, pigments and hydrogen - Kurt Ziegler-Rodriguez; Eva Gonzalez-Flo; Joan García; Marianna Garfí (Environmental Impact Assessment Review, 2026)

Robust strategy for bioplastic production from cyanobacteria-enriched microbiomes: insights from gene expression and population dynamics - Beatriz Altamira-Algarra; Lin Sun; David San León Granado; Lucía Romero-Morillo; Livia Vurro; Juan Nogales; Eva Gonzalez-Flo; Joan Garcia (Chemical Engineering Journal, 2025)

Cyanobacteria microbiomes for bioplastic production: Critical review of key factors and challenges in scaling from laboratory to industry set-ups - Beatriz Altamira-Algarra; Joan Garcia; Eva Gonzalez-Flo (Bioresource Technology, 2025)

Bioplastic production by harnessing cyanobacteria-rich microbiomes for long-term synthesis - Beatriz Altamira-Algarra; Artai Lage; Ana Lucía Meléndez; Marc Arnau; Eva Gonzalez-Flo; Joan García (Science of The Total Environment, 2024)

Enhancing pigment production with cyanobacteria-rich microbiomes: Effect of light quality and exposure time - Marta Bellver; Beatriz Altamira-Algarra; Joan García; Ivet Ferrer; Eva Gonzalez-Flo (Algal Research, 2024)

Challenges, progress, and future perspectives for cyanobacterial polyhydroxyalkanoate production - Estel Rueda; Eva Gonzalez-Flo; Soumila Mondal; Karl Forchhammer; Dulce María Arias; Katharina Ludwig; Bernhard Drosg; Ines Fritz; C. Raul Gonzalez-Esquer; Sara Pacheco; Joan García (Reviews in Environmental Science and Bio/Technology, 2024)
Polyhydroxyalkanoates (PHA) are a promising bio-based alternative to traditional plastics derived from petroleum. Cyanobacteria are photosynthetic organisms that produce PHA from CO 2 and sunlight, which can potentially reduce production costs and environmental footprint in comparison to heterotrophic bacteria cultures because (1) they utilize inorganic carbon sources for growth and (2) they do not require intensive aeration for oxygenation. Moreover, supplementing precursors such as propionate, acetate, valerate, etc., can be used to obtain various copolymers with plastic customizable properties in comparison to the classical homopolymers, such as polyhydroxybutyrate, PHB. This critical review covers the latest advances in PHA production, including recent discoveries in the metabolism interplay between PHA and glycogen production, and new insights into cultivation strategies that enhance PHA accumulation, and purification processes. This review also addresses the challenges and suggests potential solutions for a viable industrial PHAs production process.

Photosynthetic species composition determines bioplastics production in microbiomes: Strategy to enrich cyanobacteria PHB-producers - Beatriz Altamira-Algarra; Artai Lage; Joan García; Eva Gonzalez-Flo (Algal Research, 2024)

The potential of wastewater grown microalgae for agricultural purposes: Contaminants of emerging concern, heavy metals and pathogens assessment - Ana Álvarez-González; Enrica Uggetti; Lydia Serrano; Gil Gorchs; Mònica Escolà Casas; Víctor Matamoros; Eva Gonzalez-Flo; Rubén Díez-Montero (Environmental Pollution, 2023)

Nature based-solutions for water reuse: 20 years of performance evaluation of a full-scale constructed wetland system - Eva Gonzalez-Flo; Xavier Romero; Joan García (Ecological Engineering, 2023)

Host preferences of coexisting Perkinsea parasitoids during coastal dinoflagellate blooms - Albert Reñé; Natàlia Timoneda; Nagore Sampedro; Elisabet Alacid; Rachele Gallisai; Jordina Gordi; Alan D. Fernández‐Valero; Massimo C. Pernice; Eva Flo; Esther Garcés (Molecular Ecology, 2021)
Parasites in aquatic systems are highly diverse and ubiquitous. In marine environments, parasite‐host interactions contribute substantially to shaping microbial communities, but their nature and complexity remain poorly understood. In this study, we examined the relationship between Perkinsea parasitoids and bloom‐forming dinoflagellate species. Our aim was to determine whether parasite‐host species interactions are specific and whether the diversity and distribution of parasitoids are shaped by their dinoflagellate hosts. Several locations along the Catalan coast (NW Mediterranean Sea) were sampled during the blooms of five dinoflagellate species and the diversity of Perkinsea was determined by combining cultivation‐based methods with metabarcoding of the V4 region of 18S rDNA. Most known species of Parviluciferaceae, and others not yet described, were detected, some of them coexisting in the same coastal location, and with a wide distribution. The specific parasite‐host interactions determined for each of the studied blooms demonstrated the host preferences exhibited by parasitoids in nature. The dominance of a species within the parasitoid community is driven by the presence and abundances of its preferred host(s). The absence of parasitoid species, often associated with a low abundance of their preferred hosts, suggested that high infection rates are reached only under conditions that favour parasitoid propagation, especially dinoflagellate blooms.

Land Uses Simplified Index (LUSI): Determining Land Pressures and Their Link With Coastal Eutrophication - Eva Flo; Esther Garcés; Jordi Camp (Frontiers in Marine Science, 2019)

Cross-Shore Environmental Gradients in the Western Mediterranean Coast and Their Influence on Nearshore Phytoplankton Communities - Gotzon Basterretxea; Francisco J. Torres-Serra; Elisabet Alacid; Sílvia Anglès; Jordi Camp; Isabel Ferrera; Eva Flo; Joan S. Font-Muñoz; Antoni Jordi; Albert Reñé; Paula M. Salgado-Hernanz; Nagore Sampedro; et al. (Frontiers in Marine Science, 2018)

An Objective Framework to Test the Quality of Candidate Indicators of Good Environmental Status - Ana M. Queirós; James A. Strong; Krysia Mazik; Jacob Carstensen; John Bruun; Paul J. Somerfield; Annette Bruhn; Stefano Ciavatta; Eva Flo; Nihayet Bizsel; Murat Özaydinli; Romualda Chuševė; et al. (Frontiers in Marine Science, 2016)